Adaptation of the Star Intrapreneur Framework to Team Performance with Knowledge Sharing Behavior Mediationand Moderationsof Organizational Culture, Job Level, and Length of Employment: A Study atPT. XYZ Division XYZ-01 - Hadisantoso, Edoardus; Bernardus, Denny; Lie, Teofilus; Sarwoko, Endi (Riviera Publishing, 2025)
In an era of dynamic industrial competition, organizations are required to adopt innovative strategies to improve team performance. The Intrapreneur Bintang Framework emerges as a strategic approach to fostering intrapreneurial behavior within organizations. However, its effectiveness has primarily been studied in SMEs, with limited empirical evidence in large-scale industries such as biotechnology. Grounded in the Knowledge-Based View (KBV), this study aims to examine the influence of the Intrapreneur Bintang Framework on Team Performance, with Knowledge Sharing Behavior (KSB) as a mediating variable and Organizational Culture as a moderating variable. This quantitative study surveyed 106 respondents from five strategic divisions at PT. XYZ (XYZ-01) and employed PLS-SEM analysis. The results indicate that the framework has a significant influence on both KSB and Team Performance, directly and indirectly. However, the mediating effect of KSB is partial and weaker than the direct path. Organizational Culture did not significantly moderate the relationship. Similarly, the control variables of Position Level and Tenure yielded non-significant results, although coefficient directions suggest that junior and non-managerial employees are more responsive to intrapreneurial values. Theoretically, these findings extend the KBV framework by emphasizing the role of social and cultural dynamics in knowledge sharing. Practically, organizations should cultivate a systematic and organization-wide knowledge-sharing culture. Therefore, future research is encouraged to explore how each dimension of the Intrapreneur Bintang Framework can be adapted or restructured, both for upper- and lower-level employees, so that the framework remains relevant and holistic across all organizational layers